Challenges of Using English for Non-Native Entrepreneurs - Nurhikmawati Mus (Lingedu: Journal of Linguistics and Education, 2025)
This study examined the challenges that non-native English-speaking entrepreneurs encounter when using English for business communication, particularly in international settings. As English remained the dominant language in global business, these entrepreneurs had to deal with various barriers, including linguistic, cultural, and psychological obstacles that affected their performance. Through a qualitative method involving interviews and literature review, the research identified common issues such as limited vocabulary, fear of miscommunication, and low confidence during negotiations. The results showed that, although English was crucial for entering international markets, the difficulties were considerable and required effective solutions. The study also highlighted the importance of addressing these challenges by offering better language education, access to supportive technology, and policy changes. These recommendations aimed to help non-native entrepreneurs improve their communication skills and succeed in global business environments.